Evaluasi Penerapan Metode Full Costing Terhadap Akurasi Penetapan Harga Pokok Produksi Pada Sektor Peternakan Ayam Petelur - Subaidi, Ahmad; Abdani, Fadlil; Annas, Hafidhun (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to analyse the application of the full costing method in determining the cost of production at UD. Barokah Jaya, a layer chicken farming business located in Malang Regency. The urgency of this research arises from the need to understand how effective cost management can increase business profitability, especially in the context of increasingly fierce competition in the livestock industry. The research method used was qualitative with a descriptive approach. Data collection was conducted through in-depth interviews with owners and employees, direct observation of the production process, and documentation of the company's financial and operational data. Data analysis was conducted by categorising the information obtained, identifying cost components, and comparing the results of calculations using the full costing method with previously applied methods. The research findings show that the application of the full costing method provides a more comprehensive picture of production costs, thus assisting management in making more informed selling price decisions. The results and discussion indicate that by using this method, UD. Barokah Jaya can identify cost components more accurately, improve operational efficiency, and maximise profitability. As a recommendation, it is suggested that the company continue to implement and develop the full costing method, as well as conduct training for employees related to cost management to improve financial performance in the future. This research is expected to serve as a guide for similar businesses in applying more effective methods in cost management